Kajian Hubungan Tutupan Vegetasi dan Sebaran Burung di Pulau Moti, Ternate, Maluku Utara - Utaminingrum, Hetty I.P.; Sulistyadi, Eko (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTStudy on the relationships between vegetation coverage and bird distribution in Moti Island,Ternate, North Moluccas. Research study on relationships between vegetation coverage andbird distribution in Moti Island, Ternate, Moluccas was conducted on May 2010. The objectiveof this research is to understand the bird species occurrence on a vegetation type as anindicator for environment quality determination in small Moti Island. Data on the occurrenceof bird species in the every vegetation type was collected and recorded using explorationmethod. The bird species were identified for the scientific name, local name, their activities,location or coordinate position and their vegetation or habitat. The data then compiled andtabulated for the spatial analyses using Ikonos image and topographic (SRTM) maps data.The data output from the spatial analyses then analyzed using Principle Component Analyses(PCA) to get the most important factors of vegetation cover types that influenced the occurrenceof the bird species. The results showed that about 34 bird species, belong to 20 families and 29genera have occurred in the Moti Island. About 13 vegetation types were recorded as naturalsites of bird species for feeding, playing and breeding grounds. Analyzing data using PCAshowed that at least 3 vegetation types have played as important sites for bird species in thisarea. The sites were mangrove, secondary forest and mixed gardens. The roles of both threeimportant vegetation types and bird species as environment quality indicators were in detaildiscussed in this paper. The discussion also includes how to develop fisherman villages inMoti Island using its own natural resources and biodiversity.Key words: Moti Island, birds distribution, vegetation coverage, spatial analyses